PONDOK PESANTREN MUSTHAFAWIYAH PURBA BARU RELEVANSINYA DALAM REGENERASI ULAMA DI KABUPATEN MANDAILING NATAL - Muhammad Roihan Daulay (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2018)
This study to determine the relevance of IBSMPB to the regeneration of the Mandailing Natal scholars. This used a qualitative method with a fenomena approach by using qualitative descriptive analysis. As the result of the research, regeneration in Mandailing Natal Regency includes two things: culture that is physical and non-physical. As for the physical form of culture such as: long white shirt, sarong (abid), white coat, turban, robe and coat, sandals. Non-physical includes: reading the yasin on Friday, reading the takhtim and tahlil on the grave of the sholar, and visiting the house of the favorite sholar.